Benign broncho-esophageal fistula in an adult - Singh, KN; Pradhan, S; Thapa, B; Shrestha, UK; Sayami, Parveen (Journal of Institute of Medicine Nepal, 2010)
Tracheo-esophageal and broncho-esophageal fistulas are usually diagnosed early in life after an infant presents with difficulty in feeding or recurrent pneumonia. These conditions rarely present in adulthood. We report the case of a 65-year-old man who presented with chest discomfort and cough particularly after meals for three months. Workup including a barium esophagogram revealed broncho-esophegeal fistula. Dissection of the fistula and pedicled intercostal muscle flap repair was done. The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, August, 2009; 31:2 39-41